Homœopathy—A pilot study of the attitudes and awareness of pharmacy staff in the Stoke-on-Trent area - Davies, Maurice; Kayne, Steven (British Homeopathic Journal, 1992)
The survey was designed to study the attitudes of a sample of pharmacists, technicians and unqualified staff towards homœopathy, and their understanding of the principles involved.The most significant findings were that the majority of those who expressed a view (i.e. excluding the don't knows) were favourable to homœopathy, but there was little understanding of the subject. Most pharmacists thought that homœopathic medicines worked ‘by faith’. An urgent need for an education programme was demonstrated.
Keywords: Homœopathy,awareness; Pharmacists; Stoke-on-trent; Need for education